A Patient Self-Checkup App for COVID-19: Development and Usage Pattern Analysis - Heo, JoonNyung; Sung, MinDong; Yoon, Sangchul; Jang, Jinkyu; Lee, Wonwoo; Han, Deokjae; Kim, Hyung-Jun; Kim, Han-Kyeol; Han, Ji Hyuk; Seog, Woong; Ha, Beomman; Park, Yu Rang (JMIR Publications, 2020)
BackgroundClear guidelines for a patient with suspected COVID-19 infection are unavailable. Many countries rely on assessments through a national hotline or telecommunications, but this only adds to the burden of an already overwhelmed health care system. In this study, we developed an algorithm and a web application to help patients get screened. ObjectiveThis study aims to aid the general public by developing a web-based application that helps patients decide when to seek medical care during a novel disease outbreak. MethodsThe algorithm was developed via consultations with 6 physicians who directly screened, diagnosed, and/or treated patients with COVID-19. The algorithm mainly focused on when to test a patient in order to allocate limited resources more efficiently. The application was designed to be mobile-friendly and deployed on the web. We collected the application usage pattern data from March 1 to March 27, 2020. We evaluated the association between the usage pattern and the numbers of COVID-19 confirmed, screened, and mortality cases by access location and digital literacy by age group. ResultsThe algorithm used epidemiological factors, presence of fever, and other symptoms. In total, 83,460 users accessed the application 105,508 times. Despite the lack of advertisement, almost half of the users accessed the application from outside of Korea. Even though the digital literacy of the 60+ years age group is half of that of individuals in their 50s, the number of users in both groups was similar for our application. ConclusionsWe developed an expert-opinion-based algorithm and web-based application for screening patients. This innovation can be helpful in circumstances where information on a novel disease is insufficient and may facilitate efficient medical resource allocation.